Selected Plants as Sources of Natural and Active Ingredients for Cosmetics of the Future - Sławomir Kowalczyk; Mirosława Grymel; Janusz Bilik; Wiktoria Kula; Agata Wawoczny; Paulina Grymel; Danuta Gillner (Applied Sciences, 2024)
A clear trend of replacing synthetic cosmetic ingredients with natural ones can be observed in modern cosmetology. This entails the need to search for bioactive ingredients in the natural environment, especially in plants. This paper presents a comprehensive overview of dermatological, cosmetic, and pharmacological properties of highly potent plants, namely Acmella oleracea (A. oleracea), Centella asiatica (C. asiatica), Psoralea corylifolia (P. corylifolia), Plantago lanceolata L. (P. lanceolata L.), and Solidago virgaurea L. (S. virgaurea L.). Biological activity and phytochemical constituents are presented for all plants, but special attention is paid to ingredients of particular value to the cosmetics industry. The advantages of spilanthol and bakuchiol as a replacement for the popular botulinum toxin and retinol are discussed. Natural habitats, ethnomedical importance, cultivation area, as well as extraction methods of active plant ingredients are presented in detail. A wide spectrum of biological activity indicates the enormous potential of the presented plants in formulating new cosmetic and dermatological preparations.